2010
DOI: 10.1175/2009mwr3016.1
|View full text |Cite
|
Sign up to set email alerts
|

Using CASA IP1 to Diagnose Kinematic and Microphysical Interactions in a Convective Storm

Abstract: Data from the Collaborative Adaptive Sensing of the Atmosphere (CASA) Integrated Project I (IP1) network of polarimetric X-band radars are used to observe a convective storm. A fuzzy logic hydrometeor identification algorithm is employed to study microphysical processes. Dual-Doppler techniques are used to analyze the 3D wind field. The scanning strategy, sensitivity, and low-level scanning focus of the radars are investigated for influencing bulk hydrometeor identification and dual-Doppler wind retrievals. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Figure 19 shows that the distinct outflows associated with deep convective cells, including graupel particles, begin to appear from the end of Period A, around 1730 LST in the northern area. The graupel leading the low-level downdraft was also reported by Dolan and Rutledge (2010). Meanwhile, intensification of low-level southerly wind begins to appear from 1750 LST (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Figure 19 shows that the distinct outflows associated with deep convective cells, including graupel particles, begin to appear from the end of Period A, around 1730 LST in the northern area. The graupel leading the low-level downdraft was also reported by Dolan and Rutledge (2010). Meanwhile, intensification of low-level southerly wind begins to appear from 1750 LST (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies using polarimetric radar measurements revealed the presence of graupel particles in convective cells in association with stronger updrafts and downdrafts (Park et al 2009;Dolan and Rutledge 2010). Dolan and Rutledge (2010) demonstrated that graupel generated within updraft area led the strong downdraft by several minutes in convective cells. Adams-Selin et al (2013) simulated convective systems with and without graupel.…”
Section: Introductionmentioning
confidence: 99%
“…Seo and Krajewski, 2010;Sharif and Ogden, 2014; or applying adaptive scanning strategies to capture the most intensive part of a storm with a high degree of detail (e.g. Dolan and Rutledge, 2010).…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…(e.g., Boccippio 2002;Wiens et al 2005;Kuhlman et al 2006;Tessendorf et al 2007; Barthe et al 2010;Deierling et al 2008;Deierling and Petersen 2008;Dolan and Rutledge 2010). The theme of how lightning couples to the convective plume is extended and synthesized here by considering eddyscale aspects of the plume structure.…”
Section: A Convective Organization Of Electric Potentialmentioning
confidence: 99%